One-step synthesis of a MoS2-CuS composite with high electrochemical activity as an effective counter electrode for CdS/CdSe sensitized solar cells - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Shelke, Manjusha V. (Chemelectrochem, 2017)
Inorganic nanostructured composite materials involving metal sulfides are increasingly important in electrochemical applications like solar cells. In this research, we have developed a one-step in situ solvothermal method to synthesize a MoS2-CuS composite. MoS2 sheets increase electron-transfer ability, assisting the improvement in catalytic activity of the MoS2-CuS counter electrode. The charge-transfer resistance derived from impedance spectroscopy for the MoS2-CuS composite counter electrode at the electrode/electrolyte interface is very low, as compared to MoS2, mostly owing to the increased number of active catalytic sites for the reduction of polysulfide electrolyte. The Tafel polarization plot shows excellent electrocatalytic activity of the MoS2-CuS composite towards polysulfide electrolyte. Finally, the CdS/CdSe sensitized solar cell achieves a power conversion efficiency of about 5% upon optimization of the MoS2-CuS composition.